التعليم في الجزائر اثناء فترة الاحتلال الفرنسي 1870/1919م - احمد جوبر; د/ محمد محمدي (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة بالعربية: تبرز المذكرة أن السياسة التعليمية الفرنسية بالجزائر (1870-1919) شكلت أداة استعمارية لإخضاع الجزائريين بعد فشل القوة العسكرية، إذ استهدفت محو التعليم العربي الإسلامي وتعويضه بالمدرسة الفرنسية التي ركزت على الفرنسة والتنصير والإدماج، وقد صممت المنظومة التعليمية بما يخدم مصالح فرنسا الاقتصادية والسياسية، فخصت أبناء المستوطنين بتعليم نوعي، بينما حصر تعليم الأهالي في تكوين يد عاملة، ركزت المناهج على اللغة الفرنسية وتمجيد تاريخ فرنسا، في مقابل طمس الهوية الوطنية، كما رسخت التشريعات الاستعمارية التمييز وكرست الأمية الواسعة بين الجزائريين، وبينما خلفت هذه السياسة آثارا اجتماعية واقتصادية خطيرة كالمصادرة والضرائب وتدهور المعيشة، واصل التعليم التقليدي من كتاتيب وزوايا مقاومته عبر الحفاظ على القرآن واللغة العربية، ماساعد على صون الهوية الإسلامية والوطنية، وتخلص الدراسة إلى أن فرنسا فشلت في إدماج الجزائريين، وأن التعليم الاستعماري أسهم في تغذية الوعي الوطني الذي مهد لظهور الحركات الإصلاحية والتحررية لاحقا. الكلمات المفتاحية: التعليم الإستعماري، الهوية الوطنية، الوعي الوطني. ملخص الدراسة بالإنجليزية: The dissertation highlights that French educational policy in Algeria (1870–1919) served as a colonial tool to subjugate the population after the failure of military force. It sought to eliminate Arab-Islamic education and replace it with French schools centered on francization, Christianization, and assimilation. The system was designed to serve France’s political and economic interests, granting quality education to European settlers’ children while restricting Algerians to rudimentary schooling aimed at producing cheap labor. Curricula emphasized the French language and glorification of France, while erasing national identity. Colonial legislation institutionalized discrimination and perpetuated high illiteracy rates among Algerians. Despite the social and economic repercussions—such as land confiscation, heavy taxation, and deteriorating living conditions—traditional education in Quranic schools and zawiyas resisted, preserving Arabic, Islamic sciences, and cultural identity. The study concludes that France failed to integrate Algerians, and colonial schooling instead fostered national awareness that later contributed to the rise of reformist and nationalist movements.